PENGEMBANGAN MEDIA ULAR TANGGA BERBASIS MODEL LOK-R BERMUATAN BUDAYA LOKAL BANTEN DI KELAS IV SD - Komariah, Iis; Jamaludin, Ujang; Taufik, M. (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2025)
This study aims to determine the feasibility, student responses, and to determine the increase in students' understanding of Banten local culture after using the Snakes and Ladders Media Based on the LOK-R Model Containing Banten Local Culture. The study used the Research and Development (R&D) approach with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data collection techniques in the study were interviews, observations, questionnaires, tests, and documentation. The subjects of this study were grade IV students of SDN Sukamanah. The results of the study showed that the validation of material experts obtained a percentage of 93%, expert validation 89%, and language expert validation 93%, all three were included in the